Vedolizumab for perianal Crohn's disease: a multicentre cohort study in 151 patients. Issue 7 (20th February 2020) - Chapuis‐Biron, Constance; Bourrier, Anne; Nachury, Maria; Nancey, Stéphane; Bouhnik, Yoram; Serrero, Mélanie; Armengol‐Debeir, Laura; Buisson, Anthony; Tran‐Minh, My‐Linh; Zallot, Camille; Fumery, Mathurin; Bouguen, Guillaume; et al.
Summary: Background: The management of Crohn's disease patients with perianal lesions and anti‐TNF failure is challenging. Aims: To assess the effectiveness of vedolizumab in perianal Crohn's disease and the predictors of success in a real‐life cohort. Methods: We conducted a nationwide multicentre cohort study in patients with perianal Crohn's disease who received vedolizumab. In patients with active perianal Crohn's disease, the success of vedolizumab was defined by clinical success (no draining fistula at clinical examination and no anal ulcers for primary lesions) at 6 months without medical or surgical treatment for perianal Crohn's disease. Logistic regression analyses were performed to identify predictors of success. In patients with inactive perianal Crohn's disease, recurrence was defined by the occurrence of lesions and/or the need for medical or surgical treatments. Results: One hundred and fifty‐one patients were included. Among them 102 patients had active perianal disease, 33 (32.4%) males, mean age 39.8 years, mean Crohn's disease duration 14.6 years; 101 (99%) had received at least one anti‐TNF. The median follow‐up time was 52 weeks. Sixty‐eight per cent of patients discontinued therapy after a median time of 33 weeks. Vedolizumab success was reached in 23/102 (22.5%). Among patients with setons at initiation, 9/61(15%) had a successful removal. In multivariable analysis, factors associated with success were the number of prior biologic agents (≥3, odds ratio, OR: 0.20, 95% CI 0.04‐0.98) and no antibiotics at initiation (OR: 4.76, 95% CI 1.25‐18.19). In 49 patients with inactive perianal Crohn's disease, perianal disease recurred in 15/49 (30.6%), 11/49 (22.4%) needed dedicated treatments. Median time to recurrence was 22 weeks. Conclusions: We identified a low rate of success of vedolizumab in patients with active perianal Crohn's disease, and nearly one third of patients with inactive perianal Crohn's disease had perianal recurrence. Further evaluation is warranted in prospective studies.